2017
DOI: 10.1590/2177-9465-ean-2016-0361
|View full text |Cite
|
Sign up to set email alerts
|

Influence of socio-economic conditions and maternal knowledge in self-effectiveness for prevention of childhood diarrhea

Abstract: Objective: To verify the association among socioeconomic conditions, maternal behaviors and knowledge with their self-efficacy to prevent childhood diarrhea. Method: Analytical, quantitative study. Interviews were conducted with 238 mothers of children under five admitted into a hospital from January to April 2016. Were collected Sociodemographic data, maternal knowledge on prevention and management of childhood diarrhea, and application of the Maternal Self-Efficacy Scale for Childhood Diarrhea. Referente ao… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
9
0
9

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 15 publications
6
9
0
9
Order By: Relevance
“…Faktor lain yang yang merupakan elemen penting dalam menurunkan prevalensi diare di masyarakat adalah jenjang pendidikan. Masyarakat dengan pendidikan yang tinggi, akan mudah menerima informasi dan pengetahuan baru sehingga bisa menurunkan kemungkinan terkena diare (Semba et al, 2011;Woldu, Bitew and Gizaw, 2016;Hutton and Chase, 2017;Oliveira et al, 2017;Sintayehu et al, 2019). Masyarakat dengan pendidikan tinggi, cenderung lebih menanamkan dan melaksanakan perilaku hidup sehat Sedangkan masyarakat dengan pendidikan rendah, perilaku hidup sehat yang dilakukan hanya berdasarkan pengalaman tanpa mempertimbangkan dan menganalisis akibat yang terjadi.…”
Section: Hasilunclassified
“…Faktor lain yang yang merupakan elemen penting dalam menurunkan prevalensi diare di masyarakat adalah jenjang pendidikan. Masyarakat dengan pendidikan yang tinggi, akan mudah menerima informasi dan pengetahuan baru sehingga bisa menurunkan kemungkinan terkena diare (Semba et al, 2011;Woldu, Bitew and Gizaw, 2016;Hutton and Chase, 2017;Oliveira et al, 2017;Sintayehu et al, 2019). Masyarakat dengan pendidikan tinggi, cenderung lebih menanamkan dan melaksanakan perilaku hidup sehat Sedangkan masyarakat dengan pendidikan rendah, perilaku hidup sehat yang dilakukan hanya berdasarkan pengalaman tanpa mempertimbangkan dan menganalisis akibat yang terjadi.…”
Section: Hasilunclassified
“…The results of the present study support with (Joventino et al, 2013) they mention that The sociodemographic characteristics of study children with previous diarrhea show significantly precarious water management 86 (67.2), and toilet latrine with flushing 19 (55.6) [13] , soap near the tap 230 (58.5), covered of water reservoir 182 (61.9) and not a few of the respondents responded by throwing waste into the river, and accounted 14 (73.7) and agree with study conducted by (Oliveira et al, 2017). In their titled (influence of socio-economic conditions and maternal knowledge in self-effectiveness for prevention of childhood diarrhea) who reported that the most of them used flushing for toilet accounted 87 (56.1) and exclusive breastfeeding formed 119 (50.4) [14] .…”
Section: Discussion Of the Factors Related To Home Management To Stop Diarrhea (In The Table 2)mentioning
confidence: 70%
“…A prevenção da diarreia infantil está intimamente relacionada com ações executadas pelos cuidadores das crianças, sobretudo pelas mães, já que com base na influência dos cuidados maternos prestados a esta população, admite-se o seu protagonismo na redução dos índices de diarreia infantil. (24) Assim, é indispensável que as mesmas sejam orientadas quanto à prevenção de diarreia infantil e sintam-se capazes de prestar um cuidado adequado aos seus filhos, pois acredita-se que mães com autoeficácia elevada e instruídas, se sentirão capazes de reconhecerem os fatores de risco, de prevenirem e de tomarem condutas adequadas diante dessa patologia nas crianças, promovendo, dessa forma, um cuidado de maior qualidade aos seus filhos.…”
Section: Discussionunclassified
“…Pesquisa realizada no Ceará, Brasil com mães de crianças menores de cinco anos de idade identificou que as condições socioeconômicas, comportamentais e conhecimentos maternos teve associação com a ocorrência de diarreia infantil e com a autoeficácia para prevenção da diarreia infantil. (24) Corroborando com os dados das tabelas 1 e 2, ensaio clínico randomizado, realizado em Fortaleza, Ceará, Brasil, com 133 mães de crianças menores de cinco anos, sendo 70 alocadas no grupo de com-paração e 63 no grupo de intervenção identificou que, após a intervenção com vídeo educativo, houve elevação dos escores de autoeficácia em prevenir a diarreia e redução dos episódios diarreicos. (25) Diante desses achados percebe-se a importância dos profissionais e pesquisadores desenvolverem tecnologias e estratégias educativas que fortaleçam o conhecimento e a autoeficácia dos indivíduos, incentivando as mães e/cuidadores a adotarem comportamentos saudáveis a fim de prevenir a diarreia de seus filhos.…”
Section: Discussionunclassified